Mediation Effect of Motivation on Learning Achievement - A.T. Hendrawijaya (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
The level of education of parents is a major factor for students’ learning achievement. In addition to education, parents' socioeconomic status, learning environment and learning facilities also affect students learning if these factors are mediated by students’ learning motivation. This study aims to analyze and evaluate the effect of education, socioeconomic status, learning environment, and learning facilities on students’ learning achievement viewed from direct and indirect effects by the mediation of learning motivation. The research used explanatory research type involving samples from grade XI students of State Senior High Schools in the City of Jember in the academic year 2017/2018 in a total of 206 respondents. The study applied primary data collected by questionnaires, in addition to observation and documentation. The analytical tool used was path analysis to determine the direct and indirect effects. The results of the study showed that parents’ education, socioeconomic status, learning environment, learning environment and learning facilities directly affect learning motivation. Meanwhile, education, socioeconomic status, learning environment, learning facilities and learning motivation directly affect students’ learning achievement. Learning motivation mediates the effect of education, socioeconomic status, learning environment, and learning facilities on students’ achievement.